Image-Guided Cancer Therapy A Multidisciplinary Approach - Dupuy, Damian E.; Fong, Yuman; McMullen, William N. (Springer New York : Imprint: Springer, 2013)
Image-Guided Cancer Therapy: A Multidisciplinary Approach provides clinicians with in-depth coverage of the growing, dynamic field of interventional oncology.  Combining the knowledge of  expert editors and authors into one powerhouse reference, this book looks at  tumor ablation, HIFU, embolic therapies, emerging technologies, and radiation therapy throughout the body (liver, bone, breast, gynecologic  and prostate cancers, to name just a few) , and includes discussion of different imaging modalities.  In the words of Peter Mueller, MD, author of the book's Foreword:   "... The senior authors are all world renowned experts in interventional oncology, which is another example of the high quality authorship and experience that is brought to this book.  The later chapters discuss therapies that are simply not covered in any other source.  Everyone who is doing or wants to do ablation therapies and interventional oncology will face a time when they will be asked to use their expertise in less used and less investigated areas.  There is nowhere else where the reader can get information on the prostate, breast, and gynecologic areas, and especially pediatrics....This book is an outstanding contribution to the literature and will become a 'must read' for all physicians who are interested in Interventional Oncology.".